Reliability and effect of sodium bicarbonate: buffering and 2000-m rowing performance - Carr, A. J.; Slater, G. J.; Gore, C. J.; Dawson, B.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The aim of this study was to determine the effect and reliability of acute and chronic sodium bicarbon- ate ingestion for 2000-m rowing ergometer performance (watts) and blood bicarbonate concentration [HCO3 -]. Methods: In a crossover study, 7 well-trained rowers performed paired 2000-m rowing ergometer trials under double-blinded conditions: (1) 0.3 grams per kilogram of body mass (g/kg BM) acute bicarbonate; (2) 0.5 g/ kg BM daily chronic bicarbonate for 3 d; and (3) calcium carbonate placebo, in semi-counterbalanced order. For 2000-m performance and [HCO3 -], we examined differences in effects between conditions via pairwise comparisons, with differences interpreted in relation to the likelihood of exceeding smallest worthwhile change thresholds for each variable. We also calculated the within-subject variation (percent typical error). Results: There were only trivial differences in 2000-m performance between placebo (277 ± 60 W), acute bicarbonate (280 ± 65 W) and chronic bicarbonate (282 ± 65 W); however, [HCO3 -] was substantially greater after acute bicarbonate, than with chronic loading and placebo. Typical error for 2000-m mean power was 2.1% (90% confidence interval 1.4 to 4.0%) for acute bicarbonate, 3.6% (2.5 to 7.0%) for chronic bicarbonate, and 1.6% (1.1 to 3.0%) for placebo. Postsupplementation [HCO3-] typical error was 7.3% (5.0 to 14.5%) for acute bicarbonate, 2.9% (2.0 to 5.7%) for chronic bicarbonate and 6.0% (1.4 to 11.9%) for placebo. Conclusion: Performance in 2000-m rowing ergometer trials may not substantially improve after acute or chronic bicarbonate loading. However, performances will be reliable with both acute and chronic bicarbonate loading protocols.